22.4k views
5 votes
Solve for x: 3.8x − 2(x − 9) = 4.4x + 5

User Niteshb
by
4.7k points

2 Answers

6 votes

Answer:

5

Explanation:

Step 1:

3.8x - 2 ( x - 9 ) = 4.4x + 5

Step 2:

3.8x - 2x + 18 = 4.4x + 5

Step 3:

1.8x + 18 = 4.4x + 5

Step 4:

18 = 2.6x + 5

Step 5:

13 = 2.6x

Answer:

5 = x

Hope This Helps :)

User Mismas
by
5.1k points
7 votes

Answer:


x=5

Explanation:

So we have the equation:


3.8x-2(x-9)=4.4x+5

Distribute the -2:


3.8x+(-2x+18)=4.4x+5

Combine like terms on the left:


1.8x+18=4.4x+5

Subtract 1.8x from both sides. The left cancels:


18=2.6x+5

Subtract 5 from both sides. The right cancels:


13=2.6x

Divide both sides by 2.6:


x=13/2.6

Simplify (multiply both layers by 10 to get rid of the decimal):


x=130/26

Reduce (divide both layers by 26):


x=5

So, the value of x is 5.

User Bradjcox
by
4.8k points